2018
DOI: 10.1017/s0003055418000138
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Segregation and Public Goods: Evidence from Indonesia

Abstract: This article contributes to the study of ethnic diversity and public goods provision by assessing the role of the spatial distribution of ethnic groups. Through a new theory that we callspatial interdependence, we argue that the segregation of ethnic groups can reduce or even neutralize the “diversity penalty” in public goods provision that results from ethnic fractionalization. This is because local segregation allows communities to use disparities in the level of public goods compared with other communities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…By looking at how decentralization affects the provision of educational assistance to public and private schools, we contribute to the literature on decentralization and social assistance (Bardhan and Mookherjee 2005). To unravel the key mechanism through which we argue for the indication of collusion between school authorities and village officials, we position our argument within the literature on the effects of social and ethnic fragmentation on public service delivery (Alesina et al 2014;Tajima, et al 2017), particularly on the concept of rent-seeking behaviour (Mueller 2004;Cheikbossian 2008). We also explore the role of community, which relates to the literature on community engagement in development and public service delivery (Stiglitz 2002;Bovaird 2007) and in improving education quality in particular (Kendall 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By looking at how decentralization affects the provision of educational assistance to public and private schools, we contribute to the literature on decentralization and social assistance (Bardhan and Mookherjee 2005). To unravel the key mechanism through which we argue for the indication of collusion between school authorities and village officials, we position our argument within the literature on the effects of social and ethnic fragmentation on public service delivery (Alesina et al 2014;Tajima, et al 2017), particularly on the concept of rent-seeking behaviour (Mueller 2004;Cheikbossian 2008). We also explore the role of community, which relates to the literature on community engagement in development and public service delivery (Stiglitz 2002;Bovaird 2007) and in improving education quality in particular (Kendall 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Also, research has found that the effectiveness of public goods provision depends on the degree of ethnic or religious fragmentation in a society. This is particularly relevant in the case of Indonesia, where there are hundreds of ethnic groups (Alesina et al 2014;Tajima et al 2017). The impact of decentralization on the provision of goods or services will thus depend on the heterogeneity of preferences of communities.…”
Section: Rent-seeking Behaviour Within Local Institutionsmentioning
confidence: 99%
“…To generate implications that allow us to test this redistributive mechanism more directly, we turn to the literature on public goods provision in ethnically heterogeneous societies. This literature has established that public goods provision in ethnically diverse locations tends to be lower (Ejdemyr, Kramon and Robinson 2018;Tajima, Samphantharak and Ostwald 2018). It is difficult for elites, the argument goes, to identify who will profit from resource allocation if both constituency and non-constituency groups occupy the same area.…”
Section: Constituency Characteristicsmentioning
confidence: 99%
“…We build on theories about ethnic redistribution in non-conflict contexts and rent allocation in state building to answer this question (Acemoglu and Robinson 2000;Ejdemyr, Kramon and Robinson 2018;Francois, Rainer and Trebbi 2015;North, Wallis and Weingast 2009;Tajima, Samphantharak and Ostwald 2018). We theorize that in a power-sharing cabinet, rebel elitesand with them their ethnic constituentsgain access to state resources through direct cabinet-level government participation.…”
mentioning
confidence: 99%
See 1 more Smart Citation